Implementation of SWOT Analysis to Increase Competitiveness of Online Stores in the Marketplace - Refina Armelda Sari; Hapzi Ali (Siber Nusantara Review, 2024)
The advancement of digital commerce compels online sellers on marketplace platforms to adopt precise and adaptive strategies to sustain their competitiveness. This research examines key internal and external factors—namely strengths, weaknesses, opportunities, and threats (SWOT)—that shape strategic efforts in managing online stores. Utilizing a descriptive qualitative design, data were gathered through direct observation. The study indicates that a solid grasp of both internal resources and external pressures allows entrepreneurs to construct more effective strategic responses. As a result, SWOT analysis proves to be a fundamental tool for guiding the development and competitive resilience of online retail businesses operating within marketplace ecosystems.